Transient Accumulation of Nitrite Reductase mRNA in Maize following the Addition of Nitrate - Kramer, Vance (1989)
Expression of the gene coding for nitrite reductase (NiR) is induced upon the addition of nitrate. We have analyzed this induction process in hydroponically grown maize (Zea mays L.) seedlings where the level of nitrate in the medium can be easily manipulated. There is a rapid induction of NiR mRNA upon addition of nitrate, increasing first in the roots and then in the leaves. The rapidity of the response depends on the nitrate concentration and the growth medium. However, the general pattern of expression is the same: the mRNA level increases, reaches a maximum, and then decreases, despite the fact that the nitrate concentration in the medium remains constant. This decline in mRNA level can be quite rapid, particularly in root tissue. If the nitrate is given as a pulse, the mRNA levels decrease even more rapidly. It is clear that the NiR mRNA is short-lived, with a half-life in the roots of less than 30 minutes. The NiR protein level, on the other hand, increases gradually somewhat after the increase in mRNA and remains at high levels at least for 24 hours after the addition of nitrate.